Circulation of Mycobacterium tuberculosis strains of the Beijing Central Asian Outbreak genotype in the Kemerovo region — Kuzbass in 2018–2022 - Svetlana N. Zhdanova; Anna A. Vyazovaya; Irina B. Lebedeva; Vyacheslav V. Sinkov; Ilya G. Kondratov; Yakov Sh. Schwartz; Lyubov V. Rychkova; Elena B. Brusina; Igor V. Mokrousov; Oleg B. Ogarkov (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. The Kemerovo region — Kuzbass is characterized by a high prevalence of multidrug-resistant (MDR) tuberculosis (TB), including coinfection with HIV (HIV/TB). A previously unknown in Russia relationship between MDR and the Beijing Central Asian Outbreak (CAO) subtype has been discovered, which updates studies of Mycobacterium tuberculosis taking into account this resistant variant.